EDUCATIONAL DISCIPLINE PROGRAM: FROM REGIMENTATION TO EDUCATIONAL ACTIVITY DESIGNING - Natal'ya N. Shtoler; Kira L. Yaprintseva (Высшее образование в России)
The article addresses the development of the requirements for educational and methodical support of higher school educational activities. The goal of research is to characterize the evolution of the educational program (functionality, structure, use, publishing implementation) in the context of changes of the requirements for the organization and content of higher education in Russia. It is concluded that a refusal to regiment the content of disciplines is a general vector of development of educational and methodical support of the system today. At the same time there is a formalization of the requirements for the structure of the work discipline program, which ensures coherence between all the elements into an integral whole system. This process acquires particular importance in development and implementation of the current Federal State Educational Standards of higher education.